(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2022)
In the present work, we submit and study a new class AN(τ, λ, η, ρ) containing holomorphic univalent functions defined by linear operator in the open unit disk Λ=s ϵ C :|s | <1 We get some geometric properties, such as, coefficient inequality, growth, and distortion bounds, convolution properties, convex set, neighborhood property, radii of starlikeness and convexity , weighted mean and arithmetic mean for functions belonging to the class AN(τ, λ, η, ρ)